Field occurrence of high-grade metamorphic rocks at telen in the lutzow-holm complex, East Antarctica - Koizumi, T.; Tsunogae, T.; Dunkley, Daniel; Miyamoto, T.; Kato, M. (2014)
© 2014, University of Tsukuba. All Rights Reserved.We report field occurrence and brief petrographical characters of high-grade metamorphic rocks from Tel en in the granulite-facies zone of the Lützow-Holm Complex, East Antarctica, and correlate the dominant lithologies with those in adjacent exposures. The major rock types in Telen are felsic to intermediate orthogneiss, mafic granulite/amphibolite, calc-silicate rocks, felsic garnet gneiss, and pelitic granulite, which are similar to adjacent localities such as Skallen and Skallevikshalsen, although felsic to mafic orthogneisses are dominant in Telen, while calc-silicate rocks and marbles are more abundant in Skallen and Skallevikshalsen. They have monotonous N-S trending foliation dipping gently (about 20-30°) toward the east. Younger granitoids intrude nearly parallel or perpendicular to the metamorphic rocks. Peak metamorphic conditions have been estimated for a garnet-rich mafic granulite as 860-880°C and 10.1-10.5 kbar, which is consistent with the results of adjacent localities. Our study confirmed that Telen-Skallen-Skallevikshalsen region in the central domain of the granulite-facies zone corresponds to a single mass of high-grade metamorphic rocks, which was formed by Late Neoproterozoic to Cambrian high-grade metamorphism possibly related to the final phase of continent-continent collision during the assembly of Gondwana Supercontinent.